2022
DOI: 10.1080/17425247.2022.2061459
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of anti-cancer drugs using microbubble-assisted ultrasound in digestive oncology: from preclinical to clinical studies

Abstract: Introduction:The combination of microbubbles (MBs) and ultrasound (US) is an emerging method for the noninvasive and targeted enhancement of intratumor chemotherapeutic uptake. This method showed an increased local drug extravasation in tumor tissue while reducing the systemic adverse effects in various tumor models.Area covered: We focused on preclinical and clinical studies investigating the therapeutic efficacy and safety of this technology for the treatment of colorectal, pancreatic and liver cancers. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Microbubble-assisted ultrasound (MB-assisted US) is a noninvasive and targeted drug delivery method that enhances the therapeutic efficacy of anticancer drugs (e.g., chemotherapeutic drugs, oncolytic viruses, kinase inhibitors, nucleic acids, immunotherapeutics, and sonosensitizers) by increasing their intratumoral biodistribution and reducing their off-target effects [ 62 , 63 , 64 , 65 , 66 ]. In vivo, these drugs are either co-injected or injected sequentially with MBs or loaded on or into the MBs before their administration [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Microbubble-assisted ultrasound (MB-assisted US) is a noninvasive and targeted drug delivery method that enhances the therapeutic efficacy of anticancer drugs (e.g., chemotherapeutic drugs, oncolytic viruses, kinase inhibitors, nucleic acids, immunotherapeutics, and sonosensitizers) by increasing their intratumoral biodistribution and reducing their off-target effects [ 62 , 63 , 64 , 65 , 66 ]. In vivo, these drugs are either co-injected or injected sequentially with MBs or loaded on or into the MBs before their administration [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“… 10 Many preclinical studies and few clinical studies reported the use of microbubble-assisted ultrasound for the delivery of wide range of therapeutics into primary liver tumors or liver mets. 11 Schisandrin A is a bioactive lignan isolated from the traditional Chinese medicine Fructus schisandrae chinensis . Studies showed that schisandrin A had many pharmacological effects, such as anticancer, hepatoprotection, antiinflammation, which was worthy of further research and development in the future.…”
Section: Introductionmentioning
confidence: 99%
“…These biological effects lead to enhanced cellular delivery through mechanisms such as drug convection and diffusion through the pores (4-70 kDa) and endocytosis (70-500 kDa) [33][34][35]38]. Following their clinical translation as ultrasound imaging contrast agents, MB formulations have been engineered as ultrasound-responsive carriers to promote and enhance the local delivery and uptake of a wide variety of drugs [8][9][10][11], genes [12][13][14], and cells [15][16][17][18][19][20] for various therapeutic applications. Many of these applications include the delivery of therapeutic agents to treat the brain [19][20][21][22][23], heart [15,[24][25][26], and cancer [27][28][29].…”
Section: Introductionmentioning
confidence: 99%